Снятие омонимии как один из этапов синтаксической сегментации - Гаевская, Я. К.; Канищева, Ольга Валерьевна (Харьковский национальный университет радиоэлектроники, 2013)
The given work is devoted to the problem of homonymy resolution in Ukrainian language. A review of methods allowing relieve some syntactic homonymy for the Ukrainian language. The authors propose an approach based on contextual rules allows implementation of effective and fast standalone module for disambiguation during syntactic segmentation.
Keywords: синтаксический анализ; словоформа; семантические отношения; омонимы; многозначность; доминантность значения слова